Cornerstone laying of the Administration Building of the Fifth District Normal School - Unknown (Northwest Missouri State University, 1907)
Cornerstone laying of the Administration Building of the Fifth District Normal School. Ceremony included the President of the school, Homer Martin; Governor of Missouri, Joseph W. folk, Former Governor A. M. Dockery, and the Board of Regents and the area Masons no. 175 and 470.